Szczęśliwa, która uwierzyła (Łk 1,45) - Adamczewski, Bartosz (Verbum vitae, 2004)
In the Gospel scene of the Visitation Luke hints at three basie aspects ( or better to say: levels) of Mary's faith. The first one is the "parental" faith ofthe Virgin, believing that she has really become pregnant - the words of Elisabeth are for Mary the first clear evidence of this fact. The second aspect is the "theological" belief that Mary's Son will be the Messiah and the divine Deliverer of all the oppressed God's people. And finally, the "model" faith: all the disciples of Christ should imitate Mary's total and active obedience to the Word ofthe Lord, which can be transmitted somehow or other. All these aspects shape the Lucan picture o f Mary as new Abraham of the new epoch of the history o f salvation.